(untitled) (International Journal of Studies in Nursing, 2019)
Background: Breast cancer and cancer cervix contribute to high morbidity and mortality rates among women worldwide. Appropriate knowledge of both cancers can help in early detection and management. Aim: This study aimed to assess the effect of a hospital-based awareness program on the knowledge of patients attending some outpatient clinics in Sohag University Hospital regarding the 2 cancers. Subjects and Methods: The program was held in Sohag University Hospital on 150 female patients during the period between August and October 2018. The knowledge of the patients about the risk factors, symptoms, screening, and management of both cancers was first assessed using an interview questionnaire. Then, the awareness program included 4 sessions and every session discussed only 1 aspect of knowledge regarding both cancers. Later, patients were assessed again using the same questionnaire and the improvement was determined. Results: The mean age of the participating patients was 29.6 ± 6.7 years, 74.7% could read and write, and 85.3% were married. Only education was associated with better knowledge about breast cancer (p = 0.002) and cancer cervix (p = 0.007). Thanks to the program, the percent of patients with optimal knowledge of breast cancer improved from 14.7% to 50% (p <